Analisis Volatilitas Harga Daging Sapi di Kota Bandung : Pendekatan ARCH-GARCH - Syafaa, Bening Maria; Daud, Andre Rivianda; Firmansyah, Cecep (Universitas Galuh, 2025)
Fluctuating beef prices in Bandung City have an impact on economic stability. Therefore, the government is expected to form various efforts as an anticipation in maintaining beef price stability. There are parameters that need to be considered in the formation of these efforts, namely by analyzing the periods that affect price movements based on the calculation of price volatility values from ARCH-GARCH modeling. The purpose of this study is to determine the model and volatility value of beef prices, and to analyze the periods that affect the volatility value of beef prices. This research was conducted using secondary time series data obtained through a sequential survey method of beef commodity price samples for the period January 2017 to December 2024 in Bandung City. The appropriate model in calculating beef price volatility is GARCH(1,1) with an ARCH coefficient value of 0.464415 or relatively small compared to the GARCH coefficient of 0.607130, so that the volatility value of beef prices tends to increase when the variance value in the previous period is large. The factors that influence the movement of beef prices in Bandung City include the month of Ramadan and Eid al-Fitr, the imposition of restrictions on community activities due to Covid-19, and disease outbreaks that infect beef cattle, especially foot and mouth disease (FMD). Considering that most of the consumers in Bandung are middle to upper class and tourists visiting the city, the local government needs to pay attention to the beef supply at the city level.